Mid-upper arm circumference measurement for severe malnutrition screening in underfives - Stephanie Adelia; Johannes Capistrano Susanto (Paediatrica Indonesiana, 2020)
Background Severe malnutrition in Indonesia remains abundant. Severe malnutrition has been assessed by several methods, including mid–upper arm circumference (MUAC) and weight-for-height z-score (WHZ). As a screening method, MUAC is expected to be useful for identifying malnutrition in communities. Objective To determine whether MUAC measurements can be used for screening severe malnutrition at the community level in Indonesia. Method A cross-sectional study was conducted in 853 children aged 6 – 59 months who came to an integrated health service post (Posyandu) in Semarang, Central Java. Anthropometric measurements were performed by cadres and researchers and included MUAC and WHZ. Statistical analysis was done by McNemar test; results with P values >0.05 indicated no significant difference. Sensitivity and specificity were determined by 2 x 2 tables. The MUAC cut-off values were determined by receiver-operating characteristic (ROC) curve. Results Eight hundred fifty-three out of 1,115 children met the inclusion criteria, consisting of 419 (49.1%) boys, with most over the age of 2 years (57.2%). Kappa test revealed good inter-rater reliability in measurements between the cadre and researchers (Kappa=0.726). There were significant differences between MUAC (by cadres) and below red line status as well as WHZ, between MUAC (by researchers) and WHZ, as well as MUAC (by cadre and researchers) with WHZ and height-for-age z-score/HAZ . Sensitivity, specificity, PPV, and NPV of MUAC (by cadre) were 12.5%, 99.9%, 75%, and 97.5%, respectively, while those by the researchers were 16.7%, 99.6%, 57%, and 97.6%, respectively. In this study, MUAC of 14 cm was the best cut-off for severe malnutrition. Conclusion The MUAC measurement of 14 cm can be used for screening severe malnutrition in underfives at community.